Pentingnya Manajemen Kinerja Dalam Meningkatkan Produktivitas Dan Motivasi Karyawan - Moch. Iqbal Zulfikar PD (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
Performance management plays a crucial role in enhancing employee productivity and motivation in the workplace. This research employs a qualitative approach with a case study design to investigate the implementation of performance management and its impact on employee productivity and motivation in two different organizations. Organization A, a manufacturing company, implements performance management with a structured and measurable approach, while Organization B, a financial services company, adopts a more development-oriented approach. The findings reveal that both organizations successfully enhance employee productivity and motivation through effective performance management implementation. Factors such as clear goal setting, open feedback, and employee development are key to achieving positive outcomes. These findings contribute to the understanding of the importance of performance management in improving employee performance and motivation in the workplace.